Design and Feasibility Evaluation of Redux Toolkit-Based State Management in a React Reservation Prototype (CoSpace) - Hussein Nurrokhim; Alz Danny Wowor (International Journal Software Engineering and Computer Science (IJSECS), 2026)
This study examines the design and feasibility evaluation of a React-based coworking space reservation prototype named CoSpace, with Redux Toolkit applied as the state management architecture. The study was motivated by manual reservation processes that tend to produce delayed responses, recording errors, and schedule conflicts. A Research and Development (R&D) approach was employed, covering requirements analysis, system design, prototype implementation, functional testing, and user acceptance evaluation. Black Box Testing confirmed that all functional scenarios operated according to the intended design, including schedule conflict validation and role-based access restriction. User Acceptance Testing (UAT) involving 35 respondents produced an overall feasibility score of 95.4%, placing the prototype in the Very Feasible category. Within the scope of this prototype, Redux Toolkit supported centralized organization of application state and business logic — particularly through slice-based state separation and thunk-based reservation approval. The evaluation, however, was confined to a mock-data environment and did not compare Redux Toolkit against alternative state management approaches. Future work should integrate a real backend service and examine system behavior under multi-user operational conditions.